Layanan Konseling Remaja dalam Mengatasi Quarter Life Crisis Mahasiswa Tingkat Akhir - Amsal Qori Dalimunthe; Neng Nurcahyati Sinulingga; Annisaa' Fithrah; Juli Arimar (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Counseling service is an assistance carried out by a professional counselor to facilitate the development of their clients or counselors to achieve independence in realizing the ability to understand, accept, direct, and make decisions. This is very helpful for students who are experiencing a quarter life crisis, namely the heightened instability, constant change, too many choices and feelings of panic and helplessness experienced by final year students. This study uses the approach of literature review or literature review obtained from reference materials to be used as a basis for research activities. Based on the results of the study proved that by using the gestalt approach, will help individuals realize about himself so that the worry, disappointment, sadness and fear associated with his future, love, career and work as an individual is able to take responsibility and try out to find solutions in order to have confidence that he is able to succeed.